Effectiveness of duloxetine on severity of pain and quality of life in chronic low back pain in patients who had posterior spinal fixation - Arezoo Samadi; Razieh Salehian; Danial Kiani; Atefeh Ghanbari Jolfaei (Journal of Orthopaedics, Trauma and Rehabilitation)
Background: In this study, we want to search the effectiveness of Duloxetine on the severity of pain and quality of life in patients with chronic low back pain who had posterior spinal fixation. Methods: In this randomized, placebo-controlled trial done in 6 months 50 patients who had CLBP and were candidates for PSF surgery selected and divided into two groups (drug and placebo). They filled the VAS, SF-36, and Hamilton questionnaires before surgery and after 6 weeks from using 30 mg of duloxetine or placebo. Results: Significant differences were evidenced among groups for the Visual Analogue Scale (P = 0.005) and Verbal Analogue Scale (p = 0.003). Patients in the Duloxetine group have more visual and verbal pain scores than the placebo group. In the quality of life, there was a significant difference between the two groups before the intervention. Also, significant differences were evidenced among groups for the Hamilton Anxiety Rating Scale (p = 0.17). After the intervention, only the Hamilton Anxiety Rating Scale (p = 0.001) and ‘bodily pain’ and ‘general health’ subscales of quality of life (p = 0.008, 0.004, respectively) have a significant difference between the two groups. There was a significant difference between pre and post-intervention in the Hamilton Anxiety Rating Scale only in the duloxetine group. Also, in terms of quality of life, the subscales of ‘physical role’, ‘emotional role’, ‘physical pain’ and ‘total score of quality of life’ in the duloxetine and placebo groups were significantly different between pre and post-intervention. However, the subscales of ‘physical function’ and ‘general health’ were significantly different only in the duloxetine group between pre and post-intervention. Conclusion: The results suggest that the use of duloxetine in patients who had spinal surgery can help to better control back pain, on the other hand, it can cause a better psychological condition that affects the quality of life.